(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
This article identifies the characteristics of youth organizations, their main features and specifics of their activities as modern factors of world politics, the main problems and contradictions that arise in the process of their activities, as well as the main prospects for their development